Education as social policy: An introduction - Valentina Di Stasio; Heike Solga (Journal of European Social Policy, 2017)
This Special Issue considers education as a social policy in its own right, from a life-course perspective and in relation to other policy areas. It recognizes the complexity of education systems and their multi-stage architecture. The volume broadens our understanding of the role of `education as social policy' by addressing four different aspects: the importance of education providers, education as a means of social stratification, education as an interconnected regime component and public opinion on education as an important foundation of welfare state policies and a prerequisite for their sustainability in the long run. From a theoretical perspective, all authors critically engage with the social investment state approach that sees in education and training investment the lynchpin of a pre-distribution agenda protecting individuals from the new social risks of a competitive, knowledge-driven economy. The examples provided in this Special Issue expose the multifaceted role of education as social policy, drawing attention to both its formative and stratifying function across a number of European welfare states.
Keywords: 330; education; life course; public opinion; social investment state; social policy